BUKTI KEAUTENTIKAN SASTRA AMSTAL DALAM AL-QUR’AN - hafifuddin hafifuddin (UIN Sumatera Utara Medan, 2017)
The Qur'an is the holy book of life of mankind which has a high miracle. Miracles of the Qur'an in a variety of fields such as language style (mubalaghah, Ma'ani, and badi ') has the advantages that no one can beat. This discussion tries to give a brief overview of the evidence in the Qur'an's authenticity amstal literature. The method proposed is a method in the interpretation of thematic approaches that address specific themes taken from the piece of it. Alquan Qur'an as a guide to human life have drawn style and express and implied meanings are difficult to interpret without an established science. This case which led to the authenticity of the book are maintained and paradigms of human hands that want to imitate or emulate even a single verse.Keywords: Literature, Quran, and Amstal